A case study of consumers' preferences on green home attributes for sustainable lifestyle - Md Jusoh, Zuroni (Malaysian Consumer and Family Economics Association, 2015)
Green home concept is an effort to minimize the negative impact generated by conventional homes which refers to the reduction in energy use, water resources and natural resources, while providing good air quality and comfort, and produce very little residual waste. This concept is consistent with the increasing awareness in Malaysian society towards the importance of sustainable lifestyle. The aim of this study is to examine consumers’ preference on green home attributes in Peninsular Malaysia. Self-administered questionnaires were used to obtain necessary data from 600 selected households through stratified random sampling in Kajang and Bandar Baru Bangi, interviewed using two sets of questionnaires that were developed via Focus Group Discussion and Pretest sessions. The results show that the estimated implicit values for green home attributes based on Multinomial Logit regression shows that natural indoor air ventilation is the most important attribute. This is followed by green area, carbon dioxide (CO2) emission and rainwater harvesting system. The findings also reveal that Malaysian society preferred green home as compared to conventional housing based on the attributes. Finally, the study highlighted several recommendations for consumers, developers and government to stimulate the green home development in Malaysia.